Comparative connectomics: wiring diagram of a miniature insect compound eye - Randel, Nadine; Jékely, Gáspár (Current biology, 2023)
A new connectomics study of the compound eye of the miniature wasp Megaphragma viggianii highlights how the study of small animals in a comparative framework can give fresh insights into circuit evolution and function.
Online verfügbar 4 December 2023, VVersion des Artikels 4 December 2023
Gesehen am 06.03.2024